The prevailing leadership style among the leaders of public education schools in central Jeddah province from the point of view of teachers - Muharraq, Hussain Nasser Muhammad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the prevailing leadership style among the leaders of public education schools in the center of Jeddah from the point of view of teachers, and the detection of the extent of the presence of statistically significant differences due to the difference (specialization, educational stage, and years of experience).To achieve the objectives of the study, the researcher used the descriptive survey method and the use of the questionnaire as a tool was applied to a simple random sample of (348) teachers in public education schools (boys) in the center of Jeddah.The study results showed: The dominant style of leadership among public education school leaders in the center of Jeddah is the democratic style, where it obtained an overall average (2.60 out of 3), i.e. with a (high) degree of practice, then the autocratic pattern with an average of (1.50) and finally the diversionary pattern with an average of (1.36) and both with a degree of practice (low).Also, there are no statistically significant differences at the level (α ≥ 0.05) between the averages of teachers' responses due to the variables of specialization and years of experience, while there were statistically significant differences at the level (α ≥ 0.05) due to the variable of the school stage related to (the democratic style), and in favor of primary school teachers, and in the (autocratic style) and it was in favor of high school teachers.Based on the results, the researcher presented a set of recommendations, the most important of which are: Holding more training courses for school leaders regarding modern administrative trends; especially for high school leaders, in addition to proposals for complementary studies on the subject.
Keywords: the prevailing leadership style; leaders of public education schools; teachers' opinions; Jeddah governorate